Landscape and City Planning Developments in the Context of Contemporary Architecture - David Kertmenjian (Journal of Architectural and Engineering Research)
In shaping the contemporary era of architecture, the essential roles have been the primary criteria for architectural insight, among which the most important are the development of settlement types and the emergence of new building types specific to the time. The main problem is the description of the town planning crisis inherited from the 19th century, a fixation of town planning structures developed until globalization at the end of the 20th century. Objectives are the increase of population and the formation of megacities, challenges of planning regulation, and regionalization of the world, which have changed the capacity of transportation means. The state of the art is the urgency of systematization of mega settlements and the crisis of overcrowding of the population. Besides different building types, in a new sense, megacities, megastructures, and corporate and regional communication buildings have been formed. In the conclusion, climate change and newly developed environmental conditions are emphasized.